since the exclusion to an identity model of inclusion: the deficiency as biopolitical paradigm - Pagni, Pedro Angelo [UNESP] (State Univ Rio De Janeiro, 2017)
The disabled has been the subject of exclusion in the school environment. Historically, the arguments used for this would be that escape to disciplinary purposes and school, to be classified as abnormal, should be aimed at another government institution which, if not corrected, would deprive the social life. Recently, in the case of Brazil and other countries, these arguments were offset in the sense of seeking the inclusion of people with disabilities to devices and institutions that prepare for a social function and to the market. In this scenario, the category foucaultdan of biopolitics has been used by academic literature to develop a diagnostic of the role occupied by the disabilities both to discuss the so-called inclusion policies as to present alternatives to the admission of this difference in ethics institutions such as school. From this point of view, this article part of the realization of the need to improve this category, a wider diagnosis constitutive of this drawn-out between the late 1970 and the mid-1980, using other latest publications of the field foucauldians studies, to make their use a little more precise and to better focus on the place occupied by the deficiency in the current scenario biopolitics. To this end, we resorted to the studies of Robert Castel, Paul Rabinow and Francisco Ortega to re-shape the use in this category and update it in order to meet the demands of work and forms of biopower technologies emerging with inclusion policies and, specifically, to understand the conversion of disabilities as legal and administrative model in a biopolitics paradigm. We are interested in, to rebuild this course and diagnosis, show how the policies of inclusion of people with disabilities, on the one hand, meet the demands of an economic rationality implemented in neo-liberalism and, on the other, to the extent that their ethical modes of existence also are beyond the effective control of excessive life, how generate sources of experience and of resistance to this current configuration of biopolitics by creating other modes of subjectivation.
Keywords: biopolitics; inclusion; disabilities; resistance